Aplicação da técnica de grupo focal em pesquisa da Rede-SANS sobre as ações de alimentação e nutrição na atenção básica em saúde - Vieira, Carla Maria; Santiago, Laís Sartori [UNESP]; Tavare, Patrícia Cristina Wesolowski [UNESP]; Brandt, Adriana [UNESP]; Negri, Flavia; Oliveira, Maria Rita Marques De [UNESP] (Universidade Federal do Rio de Janeiro, Instituto de Estudos em Saúde Coletiva, 2013)
Focus groups are seen as important tools in qualitative research for evaluating projects aimed at articulating social networks and movements. Six focus groups were held as one of the stages in research as part of the Food Safety and Sustainable Nutrition Project (SANS). This social network articulates the academic world with social movements and government in defense of the human right to suitable nutrition. This report is aimed at discussing the experience of applying focus groups to the investigation of perceptions by health professionals of activities related to food and nutrition in basic health care. These groups made it possible to bring together 52 professionals from 13 municipalities in the State of São Paulo, Brazil, and they exchanged experiences and debated issues related to food safety in the area of health care. The group discussions identified eating, nutrition vigilance and intersectoriality as emerging topics. The focus group technique proved to be a suitable tool for investigating the topic quickly and in depth, with a large number of professionals working in different contexts. In fact, the discussions went beyond the objectives of the research, since the group work made it possible to strengthen the process of articulation carried out by a network that promoting local measures in food safety and sustainable nutrition.

Grupo focal como recurso da pesquisa qualitativa é importante ferramenta na avaliação propositiva de projetos de articulação de redes e movimentos sociais. Seis grupos focais foram aplicados como uma das etapas de pesquisa do Projeto Rede de Segurança Alimentar e Nutricional Sustentável (Rede-SANS), rede social de articulação da academia com os movimentos populares e poder público, em defesa do Direito Humano à Alimentação Adequada. Este relato teve como objetivo discutir a experiência da aplicação da referida técnica para investigar as percepções de profissionais de saúde sobre as ações de alimentação e nutrição na Atenção Básica. Os grupos focais permitiram aproximação e troca de experiências de 52 profissionais de 13 municípios de diferentes regiões do Estado de São Paulo para debater questões de segurança alimentar no contexto da área da saúde e promoveu reflexões sobre a alimentação, vigilância nutricional e intersetorialidade, como temas emergentes nos grupos. A técnica aplicada se demonstrou adequada para investigar o tema em profundidade, em pouco tempo, com um número grande de profissionais de distintos contextos para além dos objetivos da pesquisa. A realização dos grupos focais possibilitou o fortalecimento do processo de articulação de rede para a promoção de ações locais de segurança alimentar e nutricional sustentável.
Application of the focus group technique in research with the SANS network on procedures in food and nutrition in basic health care
Keywords: grupos focais; atenção primária à saúde; segurança alimentar e nutricional; programas e políticas de nutrição e alimentação; focal groups; primary health care; food and nutrition security; nutrition programs and policies